Foreword to the First Issue of the English Edition of "Urban People", a Journal of Anthropology of Urban Worlds - Soukupová, Blanka (Lidé města, 2007)
The city represents a sort of sieve of history. Its temporal layers, at first glance clear in layout, architecture, interiors, indoor and outdoor sculptures and paintings, appropriation of entire spaces, etc., are a document of the continuity of development of its territory and appearance and of important historical turning points that society and its residences pass through. Inappropriate vacant lots in crowded built-up areas in a historic center or insensitively placed constructions and structural elements, however, on first glance also bear witness to the importance people attributed and attribute to the cities’ past. It must willy nilly blend with the spirit of the time and that spirit often not only demanded reconstruction of old buildings and their surroundings and therefore helped maintain material for what we can call the memory of a city, but it also determined what to demolish, reconstruct, or change. Modern and post-modern times of a city were then affected by a conflict between so-called traditionalists and so-called modernists. Truly scholarly interest in monuments actually began only in modern national societies.